Design And Creation Of A Web-Based Non-Medical Logistics Information System At The Jakarta Heart Hospital - Reynaldy, Rio; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2024)
Jakarta Heart Center (JHC) is an agency engaged in health services, especially in dealing with heart disease. At JHC currently still does not have a non-medical logistics information system, the system used at this time is still done manually, namely to make non-medical logistics planning where officers must check directly to the warehouse where goods are stored so that it can slow down the non-medical logistics planning process itself, because it takes a long time. To deal with these problems, a web-based non-medical logistics information system was designed and built using Unified Modeling Language (UML) system modeling, PHP as a programming language and MySQL as a database, so as to help and facilitate the non-medical logistics process.